The Effect of Compensation and Physical Work Environment on Performance at PT ABS with Job Satisfaction as an Intervening Variable - Deby Anisah; Ranthy Pancasasti (Program Studi S3 Ilmu Manajemen, 2023)
One of the determining factors for the success of a company in achieving all planned and determined targets is the quality of the human resources who work and are active in it, in this case employees. But it is also possible that there are many factors that can cause employee performance and company goals to not be achieved, which include issues regarding compensation and the physical work environment which are closely related to employee job satisfaction. These three factors are very important for the company to pay attention to, because employees need to be encouraged to perform well, it is necessary to have support, one of which is appropriate compensation and a proper and harmonious physical work environment.